Hubungan Ekspresi BRAF V600E dengan Varian Histopatologik dan Infiltrasi Limfosit pada Papillary Thyroid Carcinoma (PTC) - RZ Nizar; Dutia Gestin; Aswiyanti Asri; Husna Yetti (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2021)
BackgroundPapillary thyroid carcinoma is the most common endocrine gland malignancy that has the highest incidence rate of 60-80%. In papillarythyroid carcinoma BRAF V600E mutation plays an important role in carcinogenesis. BRAF V600E is a RAS-regulated-serine-threoninekinase and activator of the MAPK pathway cascade that functions to regulate cell proliferation, differentiation and survival. BRAFV600E mutations in PTC is associated with a high incidence of recurrence and reduced survival. The purpose of this study is to lookat the relationship of BRAF V600E expression with histopathological variants and lymphocyte infiltration in PTC.MethodsThis research was a retrospective observational cross sectional study with 40 cases of papillary thyroid carcinoma which werediagnosed in 4 Pathology Anatomy Laboratory in West Sumatera. Samples were obtained from paraffin blocks of tissue from surgeryand were reevaluated for histopathological variant and lymphocyte infiltration. Expression of BRAF V600E in tumor cell were analyzedusing immunohistochemistry staining. Bivariate statistical analysis of Chi-Square were used and p value <0,05 were consideredsignificance.ResultsPositive BRAF V600E expression was found in 24 case (60%). Positive BRAF V600E expression was mostly found in classic PTC(50%). Papillary thyroid carcinoma with lymphocyte infiltration mostly found with negative BRAF V600E expression (79.2%). Statisticalanalysis showed no significant correlation between BRAF V600E with histopathological variant (p=0.74) and no significancecorrelation between BRAF V600E expression with lymphocyte infiltration (p=0.12).ConclusionThe conclusion is BRAF V600E expression has no correlation with histological variants in papillary thyroid carcinoma and no significantcorrelation of BRAF V600E expression with lymphocyte infiltration.